ADVERTISING AND LATIN IMMIGRATION IN SPAIN. INSTITUTIONAL CAMPAIGNS AS A TOOL FOR INTEGRATION - García, Sonia Carcelén; Vázquez, Belén López; Morilla, Ana Sebastian; Garcia, Nuria Villagra (Linguagens - Revista de Letras, Artes e Comunicação, 2009)
Immigration is a phenomenon with important social consequences in Spain. It has been produced by the quick increasing in numbers of the population over the last few years. The Public Administrations undertake a vital role in favouring integration of the new residents. They develop multiple services and communicative actions with this aim. The current paper is focused on studying both, the institutional campaigns undertaken by the Community of Madrid to contribute to the integration of immigrants, and to acknowledge what is the real image the immigrants have about it, where they stand among the Latin population. The methodological approach that was followed during the research is based on a qualitative approach. Helped by discussion groups, it has been possible to deeply study to what extent social advertisement efficiently contributes in the process of integration of Latin immigrants within the Community of Madrid.